‘We Don't Have to Prove to People How We're Feeling’: Understanding the Role of Peer Support Groups in Countering Epistemic Injustices in Long COVID at a US Centre - Nandini Sarma; Sam Gage; Catherine L. Hough; Aluko A. Hope (Health Expectations)
ABSTRACT Background Long COVID, an infection‐associated chronic condition characterised by new or worsening signs or symptoms for more than 3 months after a SARS‐CoV‐2 infection, is a chronic debilitating illness which remains poorly understood. Epistemic injustice in healthcare describes the unique harms or wrongs done to a person in their capacity to share and acquire knowledge about their illness. Although the concept of epistemic injustice has been described in other chronic conditions, few studies have explored these concepts in Long COVID. Objectives (1) To understand the lived experience of epistemic injustice in adults with Long COVID who were participating in a peer support group intervention and (2) to describe the potential impact of the support group on these experiences in participants. Methods Qualitative analysis utilising inductive analysis of semi‐structured individual interviews of patients with Long COVID who participated in a peer support group intervention at an academic medical centre in Oregon, USA. Results We identified three themes that captured the lived experiences of epistemic injustice in Long COVID support group participants: (1) dismissal and disregard; (2) episodic and unpredictable symptoms and impairment, and (3) knowledge and interpretation practices. We also found that the peer support potentially impacted these experiences of epistemic injustice through (1) recognition and validation; (2) solidarity and community, and (3) information exchange and expectation setting. Conclusions Long COVID patients are at risk of experiencing epistemic injustice in seeking healthcare for this complex condition. Peer support programmes may be one approach to help counter these experiences and should be further studied as a complex intervention for improving patient‐centred care in Long COVID.